CRIMINOLOGICAL TENDENCIES OF YOUTH CRIME IN LATVIA - Kipāne, Aldona (Administrative and Criminal Justice, 2019)
In the age of risk society, the word “crime” is gaining more and more importance. Today’s rapid economic development, dynamic and rather controversial technological processes, which describe the current global environment, call for a more active response to crime as one of the top priorities. In recent years, criminal offences committed by young people, especially minors, are a priority issue for law enforcement authorities, society and the state. The term “youth crime” in criminology has been introduced relatively recently. This topic has been little studied in Latvia. The paper provides an insight into the criminological scope of youth crime. The author would like to launch a discussion on the criminological study prospect of youth crime in Latvia.The aim of the paper is to describe the phenomenon of youth crime by analysing the theoretical and practical aspects. The topicality of the study of the youth crimes’ criminological aspect is determined by the prevalence of this type of crime and the problems in identifying and prevention of it. Such tasks of the study are defined: to describe the criminological content of youth crime and to provide the criminological classification of a subject; to analyse its causes and circumstances contributing to it; to discover the content of criminological prevention. The study is based on the opinions and conclusions of scientists and different documents. Several methods of general scientific research and specific methods are used in the paper: monographic and constructive approaches, logical interpretation, statistical methods and the method of legal norms’ interpretation.The author concludes that youth crime is a complex, dynamic criminological phenomenon with certain regularities, which determine its formation and existence. The author acknowledges that criminological importance is got by early prevention measures, especially for young people whose behaviour manifests itself in a criminal inclination or takes place in a hostile or criminal environment.